2018
DOI: 10.1128/mbio.00682-18
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Encodes a Novel FLT3 Receptor Ligand Necessary for Hematopoietic Cell Differentiation and Viral Reactivation

Abstract: The ability of human cytomegalovirus (HCMV) to reactivate from latent infection of hematopoietic progenitor cells (HPCs) is intimately linked to cellular differentiation. HCMV encodes UL7 that our group has shown is secreted from infected cells and induces angiogenesis. In this study, we show that UL7 is a ligand for Fms-like tyrosine kinase 3 receptor (Flt-3R), a well-known critical factor in HPC differentiation. We observed that UL7 directly binds Flt-3R and induces downstream signaling cascades, including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 57 publications
0
67
0
Order By: Relevance
“…This new HCMV-huBLT mouse model provides an ideal system to examine the effects of different viral genes on hematopoiesis that are generally too complex for tissue culture-based systems and impossible to experimentally approach in human patients. We recently published that both HCMV UL7 and US28 are required for the expansion of the CD14 + monocyte population in the huNSG model [26,27]. This novel model system will provide a tractable in vivo system in which to determine the effect of these and other viral genes during HSCT.…”
Section: Resultsmentioning
confidence: 99%
“…This new HCMV-huBLT mouse model provides an ideal system to examine the effects of different viral genes on hematopoiesis that are generally too complex for tissue culture-based systems and impossible to experimentally approach in human patients. We recently published that both HCMV UL7 and US28 are required for the expansion of the CD14 + monocyte population in the huNSG model [26,27]. This novel model system will provide a tractable in vivo system in which to determine the effect of these and other viral genes during HSCT.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the identification of a role for SFK activity during HCMV reactivation became more intriguing in light of emerging data arguing that the virus itself was not a passive observer in the process of latency and reactivation. Very recently it has been shown that an HCMV gene product, UL7, binds to flt3 ligand receptor to drive myelopoiesis and HCMV reactivation [54]. An important component of flt3 ligand signaling is the activation of SFKs [55] which may suggest a more involved role for SFKs in viral reactivation above the recruitment of MOZ to the MIEP.…”
Section: Viral Functions Manipulating Cell Signalingmentioning
confidence: 99%
“…This new HCMV-huBLT mouse model provides an ideal system to examine the effects of different viral genes on hematopoiesis that are generally too complex for tissue culture based systems and impossible to experimentally approach in human patients. We recently published that both HCMV UL7 and US28 are required for the expansion of the CD14 + monocyte population in the huNSG model [21,22]. This novel model system will provide a tractable in vivo system in which to determine the effect of these and other viral genes during HSCT.…”
Section: Resultsmentioning
confidence: 99%